Professional Teacher's Autonomy in Learning (A SiteStudy at SMK Negeri 2 Purbalingga) - Darmastuti, Setiyani (2011)
Learning process is all teachers responsibility to develop potential students. The primary goal of the learning process is to change students' behavior based on goals that have been planed and prepared by teachers before learning activity held. Teachers are the important factors in the formal education. Therefore, they must have behavior and ability to develop their students optimally. Teachers are also required to be able to present learning not only transfer knowledge, skills, and attitude, but also have ability to improve the independence of students. This research was about professional teacher's autonomy in learning. There are three objectives of this research: 1) the characteristics of interaction between the professional teachers and other teachers at SMK Negeri 2 Purbalingga; 2) the characteristics of interaction between the professional teacher and the principal at SMK Negeri 2 Purbalingga; and 3) characteristic of the work activities of the professional teachers in learning. Type of this research is a qualitative research using ethnography approach. This research is limited on the professional teachers' autonomy in learning at SMK Negeri 2 Purbalingga. The main data found from informant such as the principal, teachers, students and other supporting facilities. Data collection method used observation, in-depth interview, and documentation. Data analysis in this research was the extension of the participation, persistence on observation, and triangulation. The results of this research are: (1) characteristic of professional teacher is emphasized on the teacher's effort to create the comfortable and fun learning condition both in the classroom and outside of the classroom. So the professional teacher is expected to be able to interact and coordinate with other colleagues in order to create a new and creative education system and condition in learning; (2) the professional teacher has the same character and able to work with the principal to improve the learning method that competent in creating qualified graduates; (3) the professional teacher has a high work activities to develop and increase the wide insight to be applied to students in school.